OPTICAL SENSOR FOR SURFACE PROFILE MONITORING OF PARABOLIC ANTENNA FOR MILLIMETER AND SUBMILLIMETER ASTRONOMY - Chechetkin, D. L.; Belyankin, I. P.; Silin, V. V.; Slavgorodskiy, S. I.; Shulga, V. M. (Видавничий дім «Академперіодика», 2016)
PACS number: 07.60-jPurpose: developing the sensor for non-contact measurement and profiling parabolic surfaces of antenna systems in the millimeter and submillimeter range with an aperture diameter up to 2 m.Design/methodology/approach: Using a high-speed CCD and photoelectric displacement transducer for determining position of light spot on the antenna surface.Findings: The experimental data show that the designed sensor provides RMS estimation accuracy for the antenna surface better than 15 microns.Conclusions: Used is the optical sensor for antenna surface measurements avoids surface damage and need to control contact sensor pressure on the measured surface.Key words: optical sensor, profile measurement, parabolic antenna, submillimeter antennaManuscript submitted 01.04.2016Radio phys. radio astron. 2016, 21(2): 148-153REFERENCES1. RUZE, J., 1966. Antenna tolerance theory – a review. Proc. IEEE. vol. 54, no. 4, pp. 633–640. DOI:https://doi.org/10.1109/PROC.1966.4784 2. PEKARSH, A. I., FEOKTISTOV, S. I., KOLYKHALOV, D. G. and SHPORT, V. I., 2011. Coordinate measuring machines and complexes. Nauka i tekhnologiya v promyshlennosti. no. 3, pp. 36–48 (in Russian). 3. ZUBAREV, Y. M., KOSAREVSKIY, S. V. and REVIN, N. N., 2011. Automation of coordinate measurements. St. Petersburg: PIMash Publ. (in Russian).